Bertold Brecht – Exile, image and Utopia - Sousa, Edson Luiz André de; Pereira, Márcio Fransen (PORTO ARTE: Revista de Artes Visuais, 2017)
This article is the result of a master's research carried out in the framework of studies on psychoanalysis, art and politics. It aims to make an articulation between elements of Bertolt Brecht's exile and his thought from the perspective of Fredric Jameson, in the book Brecht and Method (2013). Therefore, it was necessary to bring into the discussion a production from Brecht’s exile - titled Kriegsfibel.